first use any pairs of 2 equations (for example i and ii, i and iii) and equalize them by using one of the variables:
i) 2x – 3y – 2z = 4 iii) 2x +2y +z = -5
2x can be written as 3y+2z+4 from the first equation, and -2y-z-5 from the third equation.
Equalize:
3y+2z+4=-2y-z-5, group common terms: 5y+3z=-9
similarly, using i and ii, eliminate x:
i) 2x – 3y – 2z = 4 ii) x + 3y + 2z = –7
multiply the second equation by 2:
i) 2x – 3y – 2z = 4 ii) 2x + 6y + 4z = –14
thus 2x=3y+2z+4 from i and 2x=-6y-4z-14 from ii:
3y+2z+4=-6y-4z-14 9y+6z=-18
So we get 2 equations with variables y and z:
a) 5y+3z=-9 b) 9y+6z=-18
now the aim of the method is clear: We eliminate one of the variables, creating a system of 2 linear equations with 2 variables, which we can solve by any of the standard methods.
Let's use elimination method, multiply the equation a by -2:
a) -10y-6z=18 b) 9y+6z=-18 ------------------------ add the equations:
-10y+9y-6z+6z=18-18 -y=0 y=0,
thus : 9y+6z=-18 0+6z=-18 z=-3
Finally to find x, use any of the equations i, ii or iii: